Women of Nepal and post-earthquake humanitarian responses: An observation of three months - K. Bajracharya (Lowland Technology International, 2016)
The devastating 25 April, 2015 earthquake in Nepal has affected a total of 1.4 million women and girls of reproductive age in the 14 most affected districts in which 93,000 were pregnant at the time of the earthquake, with 10,000 delivering each month requiring emergency obstetric care and 1,000 to 1,500 at risk of pregnancy related complications necessitating cesarean sections. Malnutrition and poverty hit women the hardest due to their longer working hours at work and home with limited access of education, health care, and involvement in local and state government. The midwifery society of Nepal (MIDSON) has established Help Desk for a week in national maternity hospital and served 100 women with the various problems of miscarriage, less fetal movement, bloody discharge, false labor pain, transportation problem to back home etc. Latter on MIDSON has expanded with support of UNFPA to conduct mobile RH camps with Minimum Initial Service Package (MISP) to protect women and girls in Nuwakot district. 25 nurse midwives were deployed in six affected districts for 3 months with support of UNICEF.